High Intensity Jump Exercise Preserves Posture Control, Gait, and Functional Mobility During 60 Days of Bed-Rest: An RCT Including 90 Days of Follow-Up - Ritzmann, Ramona; Freyler, Kathrin; Kümmel, Jakob; Gruber, Markus; Belavy, Daniel L.; Felsenberg, Dieter; Gollhofer, Albert; Kramer, Andreas; Ambrecht, Gabriele (Frontiers in Physiology, 2018)
Physical inactivity causes a deconditioning of the human body. Concerns due to chronic bed-rest include deficits in posture and gait control, predisposing individuals to an increased fall and injury risk. This study assessed the efficiency of a high-load jump exercise (JUMP) as a countermeasure to prevent detrimental effects on gait, posture control and functional mobility. In an RCT (23 males), the effect of 60 days bed-rest without training was compared to JUMP. JUMP is characterized by plyometric executed as a high intensity interval training. Typical trainings session consisted of 4 × 10 countermovement jumps and 2 × 10 hops in a sledge jump system. We assessed sway path and muscle activity in monopedal stance, spatiotemporal, kinematic, and variability characteristics in gait, functional mobility with repeated chair-rises and Timed Up and Go (TUG). Results revealed: The JUMP group showed no significant changes after bed-rest, whereas the control group exhibited substantial deteriorations: an increased sway path (+104%, p < 0.05) was accompanied by increased co-contractions of antagonistic muscles encompassing the ankle (+32%, p < 0.05) and knee joint (45%, p < 0.05). A reduced locomotor speed (−22%, p < 0.05) was found concomitant with pathological gait rhythmicity (p < 0.05), reduced joint excursions (ankle −8%, knee −29%, p < 0.05) and an increased gait variability (p < 0.05). Chair-rising was slowed (+28%, p < 0.05) with reduced peak power (+18%, p < 0.05), and more time was needed to accomplish TUG (+39%, p < 0.05). The effects persisted for a period of 1 month after bed-rest. Increases in sway path were correlated to decreases in gait speed. The JUMP effectively preserved the neuromuscular system's ability to safely control postural equilibrium and perform complex locomotor movements, including fast bipedal gait with turns and rises. We therefore recommend JUMP as an appropriate strategy combatting functional deconditioning.